DIGITAL ENGAGEMENT AND CONSUMER ATTITUDES TOWARD RESPONSIBLE CONSUMPTION OF HEALTH AND WELLNESS PRODUCTS THROUGH ONLINE PLATFORMS IN MUMBAI REGION - Gayatri Sawant; Maumita Roy (ShodhKosh: Journal of Visual and Performing Arts, 2024)
The purpose of the study is to explore various factors that influence the purchase of health wellness products. Nowadays, consumer’s consumption of wellness products is changing drastically due to increase in the awareness of health and changing lifestyles. Digital marketing is a branch of marketing that leverages online and internet-based digital technologies to promote products and services. Its evolution began in the 1990s and gained momentum throughout the 2000s. As a modern approach to advertising, digital marketing primarily utilizes the internet to connect brands with consumers more efficiently and interactively.